A Strategy for Duty Cycle Limitation of PWM Magnetic Bearing Power Amplifier - Yong, Fenfen; Wang, Xiaohu; Hu, Teng; Li, Guilin; Li, Yanjun (Scientific Journal of Technology, 2026)
Multi-phase bridge power amplifiers can meet the multi-degree-of-freedom control requirements of magnetic levitation systems, but the problem of large current ripple restricts the improvement of control accuracy. Therefore, a four-phase bridge converter for active magnetic suspension bearings is proposed, and a reverse shared winding driving path is constructed. At the same time, opposite carrier modulation technology is adopted, making the converter operate in continuous conduction mode for most of the time during normal operation, effectively reducing current ripple. To verify the effectiveness of the scheme, simulation and experimental platforms are built. The results show that this four-phase bridge converter has the advantages of small current ripple and fewer power devices.